Effects of anaerobic and respiratory adaptation of Lacticaseibacillus casei N87 on fermented sausages production - Camprini, Lucia; Pellegrini, Michela; Comi, Giuseppe; Iacumin, Lucilla (Frontiers in Sustainable Food Systems, 2023)
Lcb. casei N87, cultivated in anaerobic (A) and respiratory (R) conditions, was used as starter cultures for the production of fermented sausages. Control without the starter culture inoculation and with the addition of 150 mg/kg of nitrate was also included. The effect on physico-chemical parameters (pH, Aw, weight loss, and color), microbial population, volatilome, proteolysis as well as the survival of the strain was evaluated during 90 days of ripening. Q-PCR and DGGE-PCR analyses demonstrated the ability of the strain used in this study to adapt to this environment and carry out the sausage’s fermentation process. The inoculation of the strain did not have any effect on the Aw values, which decreased similarly in the different samples whereas the pH was lower in A samples (5.2) and the weight loss in R samples (2.5% less than the others). The color parameters of the samples inoculated with the starter cultures were comparable to those of the control added with nitrate. The concentration of aldehydes that usually are identified as marker of oxidation processes was similar in the samples inoculated with the starter cultures adapted under respiratory conditions and in the control. On the contrary, a higher level was detected in the samples inoculated with the starter cultivated under anaerobic conditions. The proteolysis that occurred during the ripening indicates the differentiation of the A samples from the others. Nonetheless, the volatile profiles of the inoculated fermented sausages were similar. The study demonstrated that aerobic adaptation of Lcb. casei N87 starter culture gave similar color parameters and amounts of aldehydes in sausages fermentations without nitrate compared to conventional fermentations with nitrate.